1995
DOI: 10.1161/01.str.26.8.1343
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Stroke Onset

Abstract: Temporal patterns of stroke onset were observed for season, day of the week, time of day, and place in a community-based population. These findings suggest that there are periods of increased risk of stroke that may be amenable to preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
148
3
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(168 citation statements)
references
References 23 publications
13
148
3
3
Order By: Relevance
“…Similar to several ongoing therapeutic trials for WUS, we used the time since symptom recognition to select a subgroup of patients with WUS comparable with patients with STW. Studies suggest that WUS occurs predominantly in the early hours of the morning 1,8 ; therefore, the more suitable time point for defining WUS onset and for defining a therapeutic window may be that of symptom recognition rather than time since last known normal. Our findings are in accordance to the evidence that clinical and early CT findings in WUS patients are not different from patients with stroke of known onset, [9][10][11][12][13] and suggest that WUS may occur predominantly in a time period shortly before awakening.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to several ongoing therapeutic trials for WUS, we used the time since symptom recognition to select a subgroup of patients with WUS comparable with patients with STW. Studies suggest that WUS occurs predominantly in the early hours of the morning 1,8 ; therefore, the more suitable time point for defining WUS onset and for defining a therapeutic window may be that of symptom recognition rather than time since last known normal. Our findings are in accordance to the evidence that clinical and early CT findings in WUS patients are not different from patients with stroke of known onset, [9][10][11][12][13] and suggest that WUS may occur predominantly in a time period shortly before awakening.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies which could not detect a statistical significance in seasonal variation in SAH onset analyzed only a small number of SAH patients since main target of the study was ischemic stroke. 9,17,20,23) Secondly, patient selection criteria and sampling design are also important. A community-based incidence study is ideal to investigate the epidemiological aspects of 3) Ferrana, Italy 199 adm hb x 2 peaks in spring and fall (p º 0.05) Mizuno (1996) 16) Nagano, Japan 632 adm hb nm trough in July Rothwell et al (1996) 20) Oxfordshire, U.K. 33 inc cb Walter peak in spring * Results were not statistically significant when p value is not presented.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were conducted in many countries and reported that incidence of stroke has irregular time pattern, and that different frequency of occurence is observed in days of the week and in months of the year (4,5). Analysis on temporal pattern of stroke occurence can help in clarification of mehanisms that we can consider as trigers of this diseases occurence (2,4,6,7).…”
Section: Introductionmentioning
confidence: 99%